A disease beyond the aortic arch presenting as a hypertensive emergency. Issue 4 (October 2021) - Shah, Kashyap; Antoine, Marc Kervin; Durkin, Raymond; Fitzpatrick, Raymond J.
Abstract: The mid-aortic syndrome, also known as mid-aortic dysplastic syndrome or coarctation of aorta, is a rare clinical entity due to the narrowing of the distal thoracic and/or abdominal aorta and its branches. It has various causes including congenital or acquired although idiopathic is the most common cause. It is more common in children and adolescents. Here we present a unique case of a 52-year-old woman who presented with shortness of breath, chest pain, and hypertensive emergency and was found to have high-grade mid-aortic stenosis which was successfully managed with surgery with no post-operative complications and complete resolution of her symptoms. <Learning objective: Mid-aortic syndrome (MAS) is a rare syndrome with various causes and presentations. It is associated with significant morbidity and mortality if left untreated. MAS can be managed symptomatically or surgically which requires taking multiple factors (age, severity, location and length of stenosis, severity of symptoms, previous response to medical therapy, end-organ damage, and visceral vessels involvement) into consideration including patient's own preferences.>